2017
DOI: 10.1038/s41598-017-12670-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of a drug loaded electrospun patch and systemic chemotherapy in pancreatic cancer xenograft

Abstract: Pancreatic cancer has a high rate of local recurrence and poor prognosis even with adjuvant chemotherapy after curative resection. The aim of this study was to investigate if local drug delivery combined with low dose systemic chemotherapy can increase the therapeutic effect of chemotherapy while reducing systemic toxicities. Poly-L-lactic acid-based 5-FU releasing patch was fabricated by electrospinning, and its tumour killing effects were first confirmed in vitro. The 5-FU patch directly adhered to the tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Similar notions have been obtained in a recent study by tailoring the polymeric scaffold geometry in 3D grid PCL architectures where the significantly improved neurite outgrowth of the PC12 cells was successfully directed the long arm direction of the designed fibrous grid [60]. Typically, in a local drug delivery study using a biocompatible poly-L-lactic acid-based 5-FU release patch, the electrospun system has yielded a significant tumour suppression effect in murine models [61]. Apart from tuning of composition and biocompatibility of the nanofibrous cell culture scaffolds, there is accumulating evidence for the importance of electrospun fibers in other aspects of nanotechnology, such drug delivery applications, which could be suggested as a prospective application for BSM/PVA nanofibers.…”
Section: Resultssupporting
confidence: 70%
“…Similar notions have been obtained in a recent study by tailoring the polymeric scaffold geometry in 3D grid PCL architectures where the significantly improved neurite outgrowth of the PC12 cells was successfully directed the long arm direction of the designed fibrous grid [60]. Typically, in a local drug delivery study using a biocompatible poly-L-lactic acid-based 5-FU release patch, the electrospun system has yielded a significant tumour suppression effect in murine models [61]. Apart from tuning of composition and biocompatibility of the nanofibrous cell culture scaffolds, there is accumulating evidence for the importance of electrospun fibers in other aspects of nanotechnology, such drug delivery applications, which could be suggested as a prospective application for BSM/PVA nanofibers.…”
Section: Resultssupporting
confidence: 70%
“…They found that loaded gemcitabine was rapidly released within the first 10 hours followed by a sustained release over the next 134 hours, and time‐dependent inhibition of tumor spheroid growth and cell viability. Jun et al 26 , 27 fabricated a poly‐L‐lactic acid–based 5‐FU–releasing patch by electrospinning and tested the oncologic effect of the combination of a local drug patch and systemic chemotherapy. This combination treatment resulted in increased tumor suppression effects that lasted longer, as well as increased survival rate, showing potential benchmarking for future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“… 19 The application of medicinal mats for antitumors mainly remains in laboratory. 20–22 Localized medicinal patches may be a practical choice for BC with frequent local recurrence. Herein, we utilized sequential electrospinning to fabricate a multilayer mat, in which GEM and CDDP were electrospun individually in distinct layers.…”
Section: Discussionmentioning
confidence: 99%